Pengaruh Brand Ambasador Celebrity, Gaya Hidup dan Kepercayaan terhadap Proses Keputusan Pembelian ( Studi Kasus Market Place Shopee ) - Sodik Mutadun; Endang Tjahjaningsih (STIE Amkop Makassar, 2022)
This research I used to analyze influence of celebrity Brand ambassador, lifestyle and trust in the purchasing decisions proces. The object of research is market place shopee and the independent variables in the study are celebrity brand ambassador, lifestyle and trust, and dependent variable is purchasing decisions proces. The population in the research are consumer visit and buoght the product at time once at market place shopees, research takes as many samples of approximately 100 answer. The method used in taking answers in the research is purposive sampling, Results in this research show that celebrity brand ambassador has a positive and insignificant effect on purchasing decisions proces, lifestyle perceptions has a positive and significant effect on purchasing decision process, trust had a positive and significant effect on purchasing decisions process. Keywords: Purchasing decisions process, celebrity brand ambassador, lifestyle and trust